A label-free fluorescence sensor for bleomycin detection based on a cavity hairpin thioflavin T-light nucleic acid switch - Nian Luo; Xueying Li; Li Zou (Biomedical Analysis, 2025)
Accurate monitoring of bleomycin (BLM) levels in clinical samples is essential for enhancing therapeutic outcomes while minimizing potential toxicity. In this study, we present a label-free fluorescent sensor for the sensitive detection of BLM, based on a cavity hairpin nucleic acid switch that activates thioflavin T (ThT) fluorescence. The engineered switch features two CGG-AAA cavities that facilitate ThT binding and fluorescence enhancement, along with a BLM-specific cleavage site (5’-GT-3’). Upon exposure to BLM, the BLM·Fe(Ⅱ)-induced DNA cleavage disrupts the hairpin structure, resulting in ThT release and a marked reduction in fluorescence intensity. Under optimized conditions, the sensor exhibits a strong linear correlation between fluorescence intensity and the logarithmic BLM concentration within the range of 10–1000 nM, achieving a detection limit of 1.26 nM. Furthermore, successful application of the sensor in human serum samples demonstrates its potential for clinical diagnostics and biomedical research.